The Catholic epistles: critical readings - Lockett, Darian R. (Critical readings in biblical studies, 2021)
I. Introduction. 1. Introduction to the Catholic Epistles / Darian R. Lockett, Biola University, USA ; 2. Further readings -- II. Historical-critical and theological studies in the Catholic Epistles. 1. Section introduction / Darian R. Lockett, Biola University, USA. a. Compositional, exegetical, textual-critical, and background studies -- 2. The fiction of James and its sitz im leben / Dale Allison, Princeton Theological Seminary, USA ; 3. Messianic Jewish identity in James / Richard Bauckham, St Andrew's University, UK ; 4. Q and James: a source-critical conundrum / Paul Foster, University of Edinburgh, UK ; 5. Hellenization/acculturation in 1 Peter / David L. Balch, Pacific Lutheran Theological Seminary, USA ; 6. The themes of 1 Peter: insights from the earliest manuscripts (the Crossby-Schøoyen Codex Ms 193 and the Bodmer miscellaneous Codex containing P72) / David G. Horrell, University of Exeter, UK ; 7. The form and background of the Polemic in 2 Peter / J.H. Neyrey, University of Notre Dame, USA ; 8. The relationship of the Fourth Gospel shared by the author of 1 John and by his opponents / Raymond E. Brown, deceased ; 9. If anyone comes / Judith M. Lieu, University of Cambridge, UK ; 10. What was from the beginning: scripture and tradition in the Johaninne Epistles / Judith M. Lieu, University of Cambridge, UK ; 11. Jude's citation of 1 Enoch: from Tertullian to Jacob of Edessa / Jeremy F. Hultin, Union Theological Seminary, USA ; 12. Jude's Exegesis / Richard Bauckham, St Andrew's University, UK ; b. Theological and interpretive issues -- 13. Letter of James as a document of Paulinism? / Margaret M. Mitchell, University of Chicago, USA ; 14. Narrating the gospel in 1 and 2 Peter / Joel B. Green, Fuller Theological Seminary, USA ; 15. Authority to become children of God / Judith M. Lieu, University of Cambridge, UK ; 16. Cosmology in the Petrine literature and Jude / John Dennis, London School of Theology, UK ; 17. Jude's christology / Richard Bauckham, St Andrew's University, UK ; 18. Further readings -- III. Methodological approaches. 19. Section introduction / Darian R. Lockett, Biola University, USA ; 20. An assessment of the rhetoric and rhetorical analysis of the letter of James / Duane F. Watson, Malone University, USA ; 21. "Unstained by the world": purity and pollution as an indicator of cultural interaction in the Epistle of James / Darian R. Lockett, Biola University, USA ; 22. Women on the edge: new perspectives on women in the Petrine Haustafel / Betsy Bauman-Martin, St Norbert College, USA ; 23. Disgraced yet graced: the gospel of First Peter in the key of honor and shame / John H. Elliott, University of Oxford, UK ; 24. Polemic and persuasion: typological and rhetorical perspectives in the letter of Jude / J. Daryl Charles, Princeton University, USA ; 25. Further readings -- IV. Reception. 26. Section introduction / Darian R. Lockett, Biola University, USA ; 27. The product of a Petrine circle? challenging an emerging consensus / David G. Horrell, University of Exeter, UK ; 28. Acceptance into the Canon / Judith M. Lieu, University of Cambridge, UK ; 29. The Epistle of Jude in the history of heresiology / Frederik Wisse, McGill University, Canada ; 30. Further Readings.